1998
DOI: 10.1086/647748
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Management of Patients and Employees Exposed to Pertussis

Abstract: Waning pertussis immunity and spread of pertussis by asymptomatic adults contributes to increased pertussis exposures of vulnerable children. The Santa Clara Valley Medical Center had 49 pertussis exposures between July 1, 1989, and June 30, 1997, which originated in pediatric units or clinics and had an impact on the Employee Health Service (EHS) and Emergency Department (ED). We have developed a standardized protocol for management of employees and patients exposed to pertussis. The protocol includes a check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Understanding the scientific rationale for the precautions will allow HCWs to apply procedures correctly, as well as to safely modify precautions based on changing requirements, resources, or health care settings. 14,654,[680][681][682][683][684][685][686][687] One study found that the likelihood of HCWs developing SARS was strongly associated with less than 2 hours of infection control training and poor understanding of infection control procedures. 688 Education regarding the important role of vaccines (eg, influenza, measles, varicella, pertussis, pneumococcal) in protecting HCWs, their patients, and family members can help improve vaccination rates.…”
Section: Iic Education Of Health Care Workers Patients and Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the scientific rationale for the precautions will allow HCWs to apply procedures correctly, as well as to safely modify precautions based on changing requirements, resources, or health care settings. 14,654,[680][681][682][683][684][685][686][687] One study found that the likelihood of HCWs developing SARS was strongly associated with less than 2 hours of infection control training and poor understanding of infection control procedures. 688 Education regarding the important role of vaccines (eg, influenza, measles, varicella, pertussis, pneumococcal) in protecting HCWs, their patients, and family members can help improve vaccination rates.…”
Section: Iic Education Of Health Care Workers Patients and Familiesmentioning
confidence: 99%
“…35,610,689,[876][877][878] Transmission of B pertussis in health care facilities has been associated with large and costly outbreaks that include both HCWs and patients. 17,36,41,100,682,826,879,880 HCWs in close contact with infants with pertussis are at particularly high risk because of waning immunity and, until 2005, the absence of a vaccine appropriate for adults. But 2 acellular pertussis vaccines were licensed in the United States in 2005, 1 for use in individuals age 11 to 18 years and the other for use in those age 10 to 64 years.…”
Section: Iin Adjunctive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several outbreaks involving health care facilities have been reported in the past few decades, which is relevant to clinical health care education settings (Broome et al, 1981; Christie et al, 2001; Haiduven, Hench, Simpkins, & Stevens, 1998; Kurt, Yeager, Guenette, & Dunlop, 1972; Linnemann, Ramundo, Perlstein, Minton, & Englender, 1975; Swinker, 1997; Weber & Rutala, 1994; Wright, Edwards, Decker, & Lamberth, 1994). These outbreaks occurred for three main reasons: (1) failure to adequately recognize and isolate infants and children with pertussis infection; (2) failure to recognize and treat disease spread in adults, particularly health care providers; and (3) lack of control measures in place.…”
Section: Lessons Learned About Pertussis and Communicable Diseasementioning
confidence: 99%